ANALISA BEBERAPA FAKTOR YANG MEMPENGARUHI PENYALURAN DANA MODAL KERJA PADA PT. BANK MANDIRI SYARIAH INDONESIA, TBK CABANG PALEMBANG - Yunidar Erlina; Ernawati Ernawati; Kamariah Kamariah (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
Working Capital Financing is one of the products owned by Bank Mandiri Syariah Indonesia which will help the business working capital needs so that the smooth operation and business development plan will be guaranteed. Based on sharia principles with a choice of musharaka, mudharabah, murabahah and ijarah vomitiya bit tamlik contracts in accordance with the specifications for working capital requirements. In achieving the profit target obtained by Bank Mandiri Syariah, namely by incurring high costs and with high costs, it is expected to get maximum results. The problem that will be studied in this study is the extent to which the influence of several factors on the distribution of working capital funds at PT. Bank Mandiri Syariah PalembangData collection techniques used the results of interviews, field notes, and other materials. Data management techniques used were the results of interviews, observations, documentation, and library materials using descriptive analysis patterns. work of 0.05 or 0.5%. This effect when viewed is small, it indicates that the size of the company in distributing working capital funds will decrease by 0.5%. Or increase by 0.5%. Vice versa, the correlation of X2 to Y (Inventory turnover to working capital fund distribution), this can be seen from the processed data SPSS 24.0 for windows. The results of the study obtained a simple regression equation, it can be seen that several factors have a large (positive) influence on financing Working capitalKeywords: Sharia Bank, Working Capital Financing